Low velocity impact study of vacuum bag infused bouligand inspired composites - Amorim, Luís Manuel Machado (2024)
This work proposes three Bouligand-inspired layups to enhance low velocity impact (LVI) damage resistance and tolerance of convectional aircraft composite laminates. Two Bouligand-like (HL and HL_S) and one hybrid design layup, merging conventional and Bouligand architecture (HYB), were produced by vacuum bag infusion. Their performance under LVI, at 13.5, 25 and40 (J), and compression after impact (CAI) tests were evaluated and comparedwith a conventional aircraft multidirectional layup (LS) produced under identical conditions. Results demonstrated that, especially for the higher impact energy levels, both Bouligand-like laminates consistently outperformed all the other configurations, exhibiting higher load bearing capacity (peak load) and energy absorption. Additionally, the rough and poorly defined interlaminar region of Bouligand-like layups have showed to delay severe damage for higher loads and energies, dissipating all (at 13.5 J) or most of the impact energy (more than 50%) through subcritical damage mechanisms. Compared with LS laminate, Bouligand-inspired layups postponed the onset of severe damage thresholds by up to 120% in load and 66% in energy (HL laminate) while developing smaller and more localized damages. The high number of fibers aligned in the loading direction of LS laminate led to better damage tolerance.